Open Access

On general partial Gaussian sums

Journal of Inequalities and Applications20162016:295

https://doi.org/10.1186/s13660-016-1238-2

Received: 2 April 2016

Accepted: 9 November 2016

Published: 22 November 2016

Abstract

Let \(q\geq2\) be a fixed integer, \(A=A(q)\leq q\), \(B=B(q)\leq q\), and \(H=H(q)\leq q\). Define
$$\hbar(A,B,H)= \bigl\{ a\in\mathbb{Z}\mid (a,q)=1, ab\equiv1\pmod{q}, 1\leq a\leq A, 1\leq b\leq B, \vert a-b\vert \leq H \bigr\} . $$
With the aid of the estimates for the general Kloosterman sums and the properties of trigonometric sums, we obtain an upper bound of the general partial Gaussian sums over the number set \(\hbar(A,B,H)\).

Keywords

partial Gaussian sumsKloosterman sums

MSC

11L0511L40

1 Introduction

Let q, N, H, n be integers with \(q\geq2\), \(H>0\), χ be a Dirichlet character mod q and \(e(y)=e^{2\pi i y}\). The study of the following partial Gaussian sums:
$$\sum_{a= N+1}^{N+H}\chi(a)e \biggl( \frac{na}{q} \biggr) $$
is of great importance. By extending his well-known work on character sums, Burgess obtained the following.

Proposition 1

[1]

Let q be a prime and χ be a non-principal Dirichlet character mod q. Then, for any integers N, n, H, r with \(0< H< q\) and \(r\geq2\), we have
$$\sum_{a= N+1}^{N+H}\chi(a)e \biggl( \frac{na}{q} \biggr)\ll H^{1-1/r}q^{1/4(r-1)}\log^{2} q. $$

Proposition 2

[2]

Let \(q\ge2\) be an integer and χ be a primitive character mod q. Then, for any integers N, n, H with \(0< H\), we have
$$ \sum_{a= N+1}^{N+H}\chi(a)e \biggl( \frac{na}{q} \biggr)\ll H^{2/3}q^{1/8+\epsilon}. $$
(1.1)

Proposition 3

[3]

Let \(q=p^{\alpha}\) (\(\alpha>1\)) be a power of the prime \(p>3\) and χ be a non-principal Dirichlet character mod q. Then, for any integers N, n, H with \(0< H\), we have
$$ \sum_{a= N+1}^{N+H}\chi(a)e \biggl( \frac{na}{q} \biggr)\ll H^{3/4}q^{1/12}\log^{3} q. $$
(1.2)

At almost the same time, Liu [4] showed independently the following.

Proposition 4

Let q be a prime power, χ, ψ be a multiplicative and additive character mod q, respectively, with χ non-principal. Then, for any integers N, H with \(0< H\), we have
$$\sum_{a= N+1}^{N+H}\chi(a)\psi(a)\ll H^{3/4}q^{1/12+\epsilon}. $$
Now let \(q\geq2\) be a fixed integer, \(A=A(q)\leq q\), \(B=B(q)\leq q\), and \(H=H(q)\leq q\). Define
$$\hbar(A,B,H)= \bigl\{ a\in\mathbb{Z}\mid (a,q)=1, ab\equiv1\pmod{q}, 1\leq a\leq A, 1\leq b\leq B, \vert a-b\vert \leq H \bigr\} . $$
It is a direct generalization of the set of so-called H-flat numbers modq, which was studied extensively by Xi (see [5] and references therein).
This paper deals with general partial Gaussian sums of the following type:
$$G_{k}(\chi,A,B,H;q)=\sum_{a\in\hbar(A,B,H)}a^{k} \chi(a)e \biggl(\frac{na}{q} \biggr), $$
where \(k\ge0\) is an arbitrary fixed integer. For the sake of periodicity of \(e (\frac{na}{q} )\) we can also restrict n to be \(1\le n\le q\). Then with the aid of the estimates for the general Kloosterman sums and the properties of trigonometric sums, we shall obtain upper bound estimates as follows.

Theorem

Let \(q\geq2\) be an integer and χ a non-principal Dirichlet character mod q. Then
$$G_{k}(\chi,A,B,H;q)\ll A^{k}q^{1/2}d(q) \biggl( \frac{nAB d(q)}{q^{2}}+\frac{B d(q)(\log q)(\log H)}{q}+\log^{3}q \biggr), $$
which is uniformly nontrivial for any positive integer n such that \(n< q^{1/2}\).

Taking n a constant, we can immediately obtain the following.

Corollary 1

Let \(q\geq2\) be an integer and χ a non-principal Dirichlet character mod q. Then we have
$$G_{k}(\chi,A,B,H;q)\ll A^{k}q^{1/2}d(q) \biggl( \frac{AB d(q)}{q^{2}}+\frac{B d(q)(\log q)(\log H)}{q}+\log^{3}q \biggr). $$

Taking \(k=0\), \(B=q\) in Corollary 1, we obtain the following.

Corollary 2

Let \(q\geq2\) be an integer and χ a non-principal Dirichlet character mod q. Then, for any positive integers A, H such that \(A, H\le q\), we have
$$ G_{0}(\chi,A,q,H;q)\ll q^{1/2}d^{2}(q) \log^{3} q. $$
(1.3)

Remark

It is easy to see that (1.3) is stronger than (1.1) for any integer H such that \(q^{9/16+\epsilon}< H\le q\). It is also stronger than (1.2) for any integer H such that \(q^{5/9}d^{8/3}(q)< H\le q\). These results reveal that more cancelations occurred in the number set \(\hbar(A,B,H)\).

Taking \(A=H=q\) in Corollary 2, we obtain the following.

Corollary 3

Let \(q\geq2\) be an integer and χ a non-principal Dirichlet character mod q. Then we have
$$G_{0}(\chi,q,q,q;q)=\sum_{a=1}^{q} \chi(a)e \biggl(\frac {na}{q} \biggr)\ll q^{1/2}d^{2}(q) \log^{3} q. $$
This is a little stronger than the classical result of the complete Gauss sums in the case when \((n,q)>1\).

2 Some lemmas

To prove the theorem, we need the following lemmas.

Lemma 1

Let q, n, , r be integers with \(q>2\), \(q>n\), and \(\ell\ge0\). Define \(h(r,\ell;n)= \sum^{n}_{a=1}a^{\ell} e (\frac {ra}{q} )\). Then we have
$$h(r,\ell;n) \textstyle\begin{cases} =\frac{n^{\ell+1}}{\ell+1}+O(n^{\ell}),& q\mid r,\\ \ll\frac{n^{\ell}}{ \vert \sin(\pi s/q)\vert } ,& q\nmid r, \end{cases} $$
where \(s=\min(r,q-r)\) with \(1\leq r\leq q-1\).

Proof

See Lemma 3 of [6] or Lemma 2.4 of [7]. □

Lemma 2

Let q be a positive integer. Then we have
$$\bigl\vert K_{\chi}(m,n;q) \bigr\vert \leq q^{1/2}(m,n,q)^{1/2}d(q), $$
where \(K_{\chi}(m,n;q)= \sum_{a\pmod{q}}\chi(a)e (\frac{ma+n\bar{a}}{q} )\) is the general Kloosterman sum, with \(a\bar{a}\equiv1\pmod{q}\) and \((m,n,q)\) the greatest common divisor of m, n, q.

Proof

See Lemma 1 of [5]. □

3 Proof of the Theorem

Now we come to prove the theorem. Note that
$$G_{k}(\chi,A,B,H;q)=\sum_{t\leq H}\mathop{ \sum_{a\leq A,b\leq B}}_{ a-b\equiv t\pmod{q},ab\equiv1\pmod{q}}a^{k}\chi(a)e \biggl(\frac{na}{q} \biggr). $$
Applying the trigonometric sums identity
$$\sum^{q}_{a=1}e \biggl( \frac{ma}{q} \biggr)= \textstyle\begin{cases} q,& q\mid m,\\ 0 ,& q\nmid m, \end{cases} $$
we obtain
$$\begin{aligned}& G_{k}(\chi,A,B,H;q) \\ & \quad = \sum_{a\in\hbar(A,B,H)}a^{k}\chi(a)e \biggl( \frac{na}{q} \biggr) \\ & \quad = \sum_{t\leq H} \mathop{\mathop{\sum \nolimits'}_{a\leq A,b\leq B}}_{ a-b\equiv t\pmod{q},ab\equiv1\pmod{q}} a^{k}\chi(a)e \biggl(\frac{na}{q} \biggr) \\ & \quad = \frac{1}{q}\sum_{m\leq q}\sum _{t\leq H}e \biggl(-\frac {mt}{q} \biggr) \mathop{\mathop{\sum \nolimits'}_{a\leq A,b\leq B }}_{ ab\equiv 1\pmod{q}} a^{k} \chi(a)e \biggl(\frac{(m+n)a-mb}{q} \biggr) \\ & \quad = \frac{1}{q^{3}}\sum_{m\leq q}\sum _{t\leq H}e \biggl(-\frac {mt}{q} \biggr) \mathop{\mathop{\sum \nolimits'}_{a,b\leq q }}_{ ab\equiv1\pmod{q}} \chi(a)e \biggl( \frac{(m+n)a-mb}{q} \biggr) \\ & \quad\quad{} \times\sum_{c\leq A}c^{k}\sum _{r\leq q}e \biggl(\frac {r(a-c)}{q} \biggr)\sum _{d\leq B}\sum_{s\leq q}e \biggl( \frac {s(b-d)}{q} \biggr) \\ & \quad = \frac{1}{q^{3}}\sum_{r,s\leq q}\sum _{m\leq q}\sum_{t\leq H}e \biggl(- \frac{mt}{q} \biggr) \mathop{\mathop{\sum\nolimits'}_{a,b\leq q }}_{ ab\equiv1\pmod{q}} \chi(a) e \biggl(\frac{(m+r+n)a-(m-s)b}{q} \biggr) \\ & \quad\quad{} \times\sum_{c\leq A}c^{k}e \biggl(- \frac{rc}{q} \biggr)\sum_{d\leq B}e \biggl(- \frac{sd}{q} \biggr) \\ & \quad = \frac{1}{q^{3}}\sum_{r,s\leq q}\sum _{m\leq q}\sum_{t\leq H}e \biggl(- \frac{mt}{q} \biggr)K_{\chi }(m+r+n,s-m;q)h(-r,k;A)h(-s,0;B) \\ & \quad = \frac{1}{q^{3}}\sum_{m\leq q}\sum _{t\leq H}e \biggl(-\frac {mt}{q} \biggr)K_{\chi}(m+n,-m;q)h(-q,k;A)h(-q,0;B) \\ & \quad\quad{} +\frac{1}{q^{3}}\sum_{r\leq q-1}\sum _{m\leq q}\sum_{t\leq H}e \biggl(- \frac{mt}{q} \biggr)K_{\chi }(m+r+n,-m;q)h(-r,k;A)h(-q,0;B) \\ & \quad\quad{} +\frac{1}{q^{3}}\sum_{s\leq q-1}\sum _{m\leq q}\sum_{t\leq H}e \biggl(- \frac{mt}{q} \biggr)K_{\chi}(m+n,s-m;q)h(-q,k;A)h(-s,0;B) \\ & \quad\quad{} +\frac{1}{q^{3}}\sum_{r,s\leq q-1}\sum _{m\leq q}\sum_{t\leq H}e \biggl(- \frac{mt}{q} \biggr)K_{\chi}(m+r+n,s-m;q)h(-r,k;A)h(-s,0;B). \end{aligned}$$
Then from Lemma 1 and Lemma 2, we have
$$\begin{aligned}& \frac{1}{q^{3}}\sum_{m\leq q}\sum _{t\leq H}e \biggl(-\frac {mt}{q} \biggr)K_{\chi}(m+n,-m;q)h(-q,k;A)h(-q,0;B) \\& \quad \ll\frac{1}{q^{3}}\sum_{m\leq q}\min \biggl(H, \biggl\Vert \frac {m}{q} \biggr\Vert ^{-1} \biggr) \bigl\vert K_{\chi}(m+n,-m;q) \bigr\vert \cdot \bigl\vert h(-q,k;A) \bigr\vert \cdot \bigl\vert h(-q,0;B) \bigr\vert \\& \quad \ll HA^{k+1}Bq^{-5/2}d(q)\sum _{m\leq q/H}(m+n,q)^{1/2} \\& \quad\quad{} +A^{k+1}Bq^{-3/2}d(q) \sum_{q/H< m\leq q-1}\frac{(m+n,q)^{1/2}}{m}, \end{aligned}$$
where \(\Vert x\Vert =\min_{a\in Z}\vert x-a\vert \).
Combining the estimates
$$\begin{aligned} \sum_{m\leq q/H}(m+n,q)^{1/2}&=\sum _{d\mid q}d^{1/2}\mathop{\sum _{m\leq q/H }}_{ d\mid (m+n)}1 \\ & =\sum_{d\mid q}d^{1/2}\sum _{m\leq q/(dH)+n/d}1 \\ & \ll H^{-1}qd(q)+nd(q) \end{aligned}$$
and
$$\begin{aligned} \sum_{q/H< m\leq q-1}\frac{(m+n,q)^{1/2}}{m}&= \sum _{d\mid q}d^{1/2}\mathop{\sum _{q/H< m\leq q-1}}_{ d\mid (m+n)}\frac{1}{m} \\ & = \sum_{d\mid q}d^{1/2}\sum _{\frac{q}{Hd}+\frac{n}{d}< m\leq\frac {q-1+n}{d}}\frac{1}{dm-n} \\ &\ll\sum_{d\mid q}d^{-1/2}\sum _{\frac{q}{Hd}+\frac{n}{d}< m\leq\frac {q-1+n}{d}}\frac{1}{m} \biggl(1+\frac{n}{dm} \biggr) \\ &\ll d(q)\log H+nd(q), \end{aligned}$$
we have
$$\begin{aligned}& \frac{1}{q^{3}}\sum_{m\leq q}\sum _{t\leq H}e \biggl(-\frac {mt}{q} \biggr)K_{\chi}(m+n,-m;q)h(-q,k;A)h(-q,0;B) \\& \quad \ll nA^{k+1}Bq^{-3/2}d^{2}(q)+A^{k+1}Bq^{-3/2}d^{2}(q) \log H. \end{aligned}$$
(3.1)
Applying Lemma 1 and Lemma 2 again, we obtain
$$\begin{aligned}& \frac{1}{q^{3}}\sum_{r\leq q-1}\sum _{m\leq q}\sum_{t\leq H}e \biggl(- \frac{mt}{q} \biggr)K_{\chi}(m+r+n,-m;q)h(-r,k;A)h(-q,0;B) \\& \quad \ll\frac{1}{q^{3}}\sum_{r\leq q-1}\sum _{m\leq q}\min \biggl(H, \biggl\Vert \frac{m}{q} \biggr\Vert ^{-1} \biggr) \bigl\vert K_{\chi }(m+r+n,-m;q) \bigr\vert \cdot \bigl\vert h(-r,k;A) \bigr\vert \cdot \bigl\vert h(-q,0;B) \bigr\vert \\& \quad \ll HBq^{-5/2}d(q)\sum_{r\leq q-1}\sum _{m\leq q/H}(m+r+n,-m,q)^{1/2}\cdot \frac{A^{k}}{\vert \sin(\frac{\pi r}{q})\vert } \\& \quad \quad{}+Bq^{-3/2}d(q)\sum_{r\leq q-1}\sum _{q/H< m\leq q-1}\frac {(m+r+n,-m,q)^{1/2}}{m}\cdot\frac{A^{k}}{\vert \sin(\frac{\pi r}{q})\vert } \\& \quad \ll HA^{k}Bq^{-3/2}d(q)\sum _{r\leq q-1} \frac{1}{r}\sum_{m\leq q/H}(m+r+n,-m,q)^{1/2} \\& \quad\quad{} +A^{k}Bq^{-1/2}d(q)\sum _{r\leq q-1} \frac{1}{r}\sum_{q/H< m\leq q-1} \frac{(m+r+n,-m,q)^{1/2}}{m} . \end{aligned}$$
Combining
$$\begin{aligned}& \sum_{r\leq q-1}\frac{1}{r}\sum _{m\leq q/H}(m+r+n,-m,q)^{1/2} \\ & \quad =\sum_{d\mid q}d^{1/2}\mathop{\sum _{r\leq q}}_{ d\mid (r+n)}\frac{1}{r}\mathop{\sum _{m\leq q/H }}_{ d\mid m} 1 \\ & \quad =\sum_{d\mid q}d^{1/2}\sum _{(n+1)/d \le r\leq(q+n-1)/d}\frac {1}{dr-n}\sum_{m\leq q/(Hd)} 1 \\ & \quad \ll q/H\sum_{d\mid q}d^{-3/2}\sum _{(n+1)/d \le r\leq(q+n-1)/d}\frac {1}{r} \biggl(1+\frac{n}{dr} \biggr) \\ & \quad \ll H^{-1}qd(q)\log \biggl(\frac{q+n-1}{n+1} \biggr) \end{aligned}$$
and
$$\begin{aligned}& \sum_{r\leq q-1}\frac{1}{r}\sum _{q/H< m\leq q-1}\frac {(m+r+n,-m,q)^{1/2}}{m} \\ & \quad =\sum_{d\mid q}d^{1/2}\mathop{\sum _{r\leq q-1}}_{ d\mid (r+n)}\frac{1}{r}\mathop{\sum _{q/H< m\leq q-1}}_{ d\mid m}\frac{1}{m} \\ & \quad =\sum_{d\mid q}d^{-1/2}\sum _{(n+1)/d \le r\leq(q+n-1)/d}\frac {1}{dr-n}\sum_{q/(Hd)< m\leq q/d} \frac{1}{m} \\ & \quad \ll(\log H)\sum_{d\mid q}d^{-3/2}\sum _{r\leq q/d}\frac{1}{r(1-\frac {n}{dr})} \\ & \quad \ll d(q) (\log H) \log \biggl(\frac{q+n-1}{n+1} \biggr), \end{aligned}$$
we have
$$\begin{aligned}& \frac{1}{q^{3}}\sum_{r\leq q-1}\sum _{m\leq q}\sum_{t\leq H}e \biggl(- \frac{mt}{q} \biggr)K_{\chi}(m+r+1,-m;q)h(-r,k;A)h(-q,0;B) \\ & \quad \ll A^{k}Bq^{-1/2}d^{2}(q) (\log H) \log \biggl( \frac{q+n-1}{n+1} \biggr). \end{aligned}$$
(3.2)
Similarly, we get the estimate
$$\begin{aligned}& \frac{1}{q^{3}}\sum_{s\leq q}\sum _{m\leq q}\sum_{t\leq H}e \biggl(- \frac{mt}{q} \biggr)K_{\chi}(m+1,s-m;q)h(-q,k;A)h(-s,0;B) \\ & \quad \ll A^{k+1}q^{-3/2}d^{2}(q)\log \biggl( \frac{q-1}{n+1} \biggr). \end{aligned}$$
(3.3)
Noting that
$$\begin{aligned}& \frac{1}{q^{3}}\sum_{r,s\leq q-1}\sum _{m\leq q}\sum_{t\leq H}e \biggl(- \frac{mt}{q} \biggr)K_{\chi }(m+r+n,s-m;q)h(-r,k;A)h(-s,0;B) \\ & \quad \ll q^{-5/2}\tau(q)\sum_{r,s\leq q-1}\sum _{m\leq q}\min \biggl(H, \biggl\Vert \frac{m}{q} \biggr\Vert ^{-1} \biggr)\cdot (m+r+n,s-m,q)^{1/2} \frac{A^{k}}{\vert \sin(\frac{\pi r}{q})\vert }\cdot\frac{1}{\vert \sin(\frac{\pi s}{q})\vert } \\ & \quad \ll HA^{k}q^{-1/2}d(q)\sum _{r,s\leq q-1} \frac{1}{rs}\sum_{m\leq q/H}(m+r+n,s-m,q)^{1/2} \\ & \quad\quad{} +A^{k}q^{1/2}d(q)\sum _{r,s\leq q-1} \frac{1}{rs}\sum_{q/H< m\leq q-1} \frac{(m+r+n,s-m,q)^{1/2}}{m} . \end{aligned}$$
Using the estimates
$$\begin{aligned}& \sum_{r,s\leq q-1}\frac{1}{rs}\sum _{m\leq q/H}(m+r+n,s-m,q)^{1/2} \\ & \quad =\sum_{d\mid q}d^{1/2}\sum _{m\leq q/H}\mathop{\sum_{r\leq q-1}}_{ d\mid (m+r+n)} \frac{1}{r}\mathop{\sum_{s\leq q-1}}_{ d\mid (s-m)} \frac{1}{s} \\ & \quad =\sum_{d\mid q}d^{1/2}\sum _{m\leq q/H}\sum_{(m+n+1)/d \le r\leq (q+m+n-1)/d}\frac{1}{dr-m-n} \sum_{(1-m)/d\le s\leq(q-m-1)/d}\frac {1}{ds+m} \\ & \quad \ll H^{-1}q d(q) (\log q) \log(2q+n-1) \end{aligned}$$
and
$$\begin{aligned}& \sum_{r,s\leq q-1}\frac{1}{rs}\sum _{q/H< m\leq q-1}\frac {(m+r+n,s-m,q)^{1/2}}{m} \\ & \quad =\sum_{d\mid q}d^{1/2}\sum _{q/H < m\leq q-1}\frac{1}{m}\mathop{\sum _{r\leq q-1}}_{ d\mid (m+r+n)}\frac{1}{r}\mathop{\sum _{s\leq q-1}}_{ d\mid (s-m)}\frac {1}{s} \\ & \quad =\sum_{d\mid q}d^{1/2}\sum _{q/H < m\leq q-1}\frac{1}{m}\sum_{(m+n+1)/d \le r\leq(q+m+n-1)/d} \frac{1}{dr-m-n}\sum_{(1-m)/d\le s\leq (q-m-1)/d}\frac{1}{ds+m} \\ & \quad \ll d(q) \bigl(\log^{2}q \bigr) \log(2q+n-1), \end{aligned}$$
we have
$$\begin{aligned}& \frac{1}{q^{3}}\sum_{r,s\leq q-1}\sum _{m\leq q}\sum_{t\leq H}e \biggl(- \frac{mt}{q} \biggr)K_{\chi }(m+r+n,s-m;q)h(-r,k;A)h(-s,0;B) \\ & \quad \ll A^{k}q^{1/2}d(q) \bigl(\log^{2} q \bigr) \log(2q+n-1). \end{aligned}$$
(3.4)
Now combining (3.1)-(3.4), we have
$$G_{k}(\chi,A,B,H;q)\ll A^{k}q^{1/2}d(q) \biggl( \frac{nAB d(q)}{q^{2}}+\frac{B d(q)(\log q)(\log H)}{q}+\log^{3}q \biggr). $$
This completes the proof of the theorem.

Declarations

Acknowledgements

The article was supported by the National Natural Science Foundation of China (Grant Nos. 11201275, 11471258), the Research Fund for the Doctoral Program of Higher Education of China (Grant No. 20106101120001), the Natural Science Foundation of Shaanxi Province of China (Grant Nos. 2011JQ1010, 2016JM1017), the Scientific Research Program Funded by Shaanxi Provincial Education Department (Grant No. 15JK1794) and the Fundamental Research Funds for the Central Universities (Grant No. GK201503014). The authors want to show their great thanks to the anonymous referee for his/her helpful comments and suggestions.

Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

Authors’ Affiliations

(1)
College of Mathematics and Information Science, Xianyang Normal University
(2)
School of Mathematics, Northwest University
(3)
School of Mathematics and Information Science, Shaanxi Normal University

References

  1. Burgess, DA: Partial Gaussian sums. Bull. Lond. Math. Soc. 20(6), 589-592 (1988) MathSciNetView ArticleMATHGoogle Scholar
  2. Burgess, DA: Partial Gaussian sums. II. Bull. Lond. Math. Soc. 21(2), 153-158 (1989) MathSciNetView ArticleMATHGoogle Scholar
  3. Burgess, DA: Partial Gaussian sums. III. Glasg. Math. J. 34(2), 253-261 (1992) MathSciNetView ArticleMATHGoogle Scholar
  4. Liu, CL: On incomplete Gaussian sums. Acta Math. Sin. New Ser. 12(2), 141-150 (1996) MathSciNetView ArticleMATHGoogle Scholar
  5. Xi, P, Yi, Y: On character sums over flat numbers. J. Number Theory 130(5), 1234-1240 (2010) MathSciNetView ArticleMATHGoogle Scholar
  6. Xu, ZF: Distribution of the difference of an integer and its m-th power mod n over incomplete intervals. J. Number Theory 133(12), 4200-4223 (2013) MathSciNetView ArticleMATHGoogle Scholar
  7. Xu, ZF, Zhang, TP: High-dimensional D.H. Lehmer problem over short intervals. Acta Math. Sin. Engl. Ser. 30(2), 213-228 (2014) MathSciNetView ArticleMATHGoogle Scholar

Copyright

© Ren et al. 2016